Non-Invasive Multimodal Neuromonitoring in Non-Critically Ill Hospitalized Adult Patients With COVID-19: A Systematic Review and Meta-Analysis - Battaglini, Denise; Premraj, Lavienraj; Huth, Samuel; Fanning, Jonathon; Whitman, Glenn; Arora, Rakesh C.; Bellapart, Judith; Bastos Porto, Diego; Taccone, Fabio Silvio; Suen, Jacky Y.; Li Bassi, Gianluigi; Fraser, John F.; et al. (Frontiers in Neurology, 2022)
Introduction: Neurological complications are frequent in patients with coronavirus disease-2019 (COVID-19). The use of non-invasive neuromonitoring in subjects without primary brain injury but with potential for neurological derangement is gaining attention outside the intensive care unit (ICU). This systematic review and meta-analysis investigates the use of non-invasive multimodal neuromonitoring of the brain in non-critically ill COVID-19 patients outside the ICU and quantifies the prevalence of abnormal neuromonitoring findings in this population. Methods: A structured literature search was performed in MEDLINE/PubMed, Scopus, Cochrane, and EMBASE to investigate the use of non-invasive neuromonitoring tools, including transcranial doppler, TCD; optic nerve sheath diameter, ONSD; near infrared spectroscopy, NIRS; pupillometry; and electroencephalography and EEG in COVID-19 patients outside the ICU. The proportion of non-ICU COVID-19 patients with a particular neurological feature at neuromonitoring at the study time was defined as prevalence. Results: A total of 6,593 records were identified through literature searching. Twenty-one studies were finally selected, with 368 non-ICU patients included of whom 97 were considered for prevalence meta-analysis. The pooled prevalence of electroencephalographic seizures, periodic and rhythmic patterns, slow background abnormalities, and abnormal background on EEG was 0.17 (95% CI 0.04-0.29), 0.42 (95% CI 0.01-0.82), 0.92 (95% CI 0.83-1.01), and 0.95 (95% CI 0.88-1.09), respectively. No studies investigating NIRS and ONSD outside the ICU were found. Pooled prevalence for abnormal neuromonitoring findings detected using the TCD and pupillometry were non-computable due to insufficient data. Conclusions: Neuromonitoring tools are non-invasive, low-cost, safe, and bedside available tools with a great potential for both diagnosis and monitoring of COVID-19 patients at risk of brain derangements. However, extensive literature searching reveals they are rarely used outside critical care setting.